Effects of tualang honey on kainic acid-induced morphological changes and glutamate transporter (EAAT2) expression in the cerebellum and striatum of rats - Zulkifli, Nurdarina Ausi (2021)
Excitotoxicity is a type of neuronal cell death induced by excessive glutamate or other excitatory amino acids and has been implicated in various neurodegenerative diseases. The excitatory amino acid transporter 2 (EAAT2) is a major glutamate transporter responsible for nearly 90% of glutamate reuptake in the brain. Loss of EAAT2 causes accumulation of extracellular glutamate and excitotoxicity. Tualang honey (TH) is a Malaysian honey that has shown many beneficial effects in various disease models. The main objectives of this study were to evaluate the potential protective effects of Tualang honey on kainic acid-induced morphological changes and EAAT2 expression in the cerebellum and striatum of rats. A total of 48 male adult Sprague Dawley rats with the weight of 260-320g were randomly divided into four major groups (n = 12 per group) depending on the treatment received: control, KA, TH+KA and TPM+KA. Each major group was further divided into two subgroups depending on sacrifice time (24 hours or 5 days following KA administration) (n = 6 per subgroup). The rats were pre-treated orally with distilled water (groups control and KA), Tualang honey (1.0 g/kg; group TH+KA) or topiramate (40 mg/kg; group TPM+KA) for five times at 12 hours interval. The rats were then injected subcutaneously with KA (15 mg/kg; groups KA, TH+KA and TPM+KA) or normal saline (control) 30 minutes after the last oral treatment. An open field test was performed to assess the locomotor activity of rats before the rats were sacrificed at 24 hours or 5 days after the KA administration. The cerebellum and striatum were collected for histological and EAAT2 assessment. Significant reduction in the number of viable neurons and EAAT2 expression were observed in both cerebellum and striatum 24 hours following KA administration. KA-induced significant increase in locomotor activity, along with significantly reduced viable neurons in the cerebellum and EAAT2 expression in the striatum were observed 5 days following KA administration. Pre-treatment with TH increased the number of viable neurons and EAAT2 expression in the cerebellum and striatum. The effects were comparable to TPM, the control drug used in this study. These findings suggest that pre-treatment with TH showed some protective effects against KA-induced excitotoxicity via modulation of EAAT2 expression.